Evaluación del proceso de electroforesis y la estabilidad térmica de las proteínas concentradas lácteas en la empresa Alpina Productos Alimenticios S.A. (2023)
Concentrated whey proteins are a product known as Whey Protein Concentrate (WPC) obtained from whey in the food industry. Currently in Colombia this product comes only from imports, which is why together with the Colombian company Alpina Productos Alimenticios S.A.S. BIC, the opportunity was identified to add value to the whey coming from the company by transforming it into protein concentrate, reducing the acquisition costs of WPC and contributing to the technological development of the country. In order to know the state of the art regarding the valorization of cheese by-products, the project included an exhaustive bibliographic review regarding whey, filtration technologies, whey protein concentrates, thermal stability of proteins and electrophoresis.